UNLOCKING POTENTIAL: THEME-BASED LEARNING TO IMPROVE NON-ENGLISH MAJORS’ READING AND WRITING SKILLS - Putra, Hedyan; Sekewael, Mansye (University of Kuningan, 2025)
This study explores the effectiveness of theme-based learning in enhancing English reading comprehension and writing skills among non-English majors, specifically accounting students at the State Polytechnic of Ambon. Using a quasi-experimental pretest-post-test control group design, 50 fourth-semester students were divided into experimental and control groups, with the experimental group receiving 20 instructional sessions using the Theme-Based Model of Content-Based Instruction (CBI). The results demonstrated significant improvements in reading comprehension and writing skills in the experimental group, with 36% of students achieving